Macroscopic Evaluation of Poly(3-hydroxybutyrate-co-3-hydroxy valerate), PHBV-Based Nanofiber Scaffolds with Aloe Vera or Honey in Murine Wound Healing - José Manuel Pérez-Galván; José Enrique Hernández-Rodríguez; José Luis Martín-Barrasa; Maximina Monzón-Mayor; Pedro Saavedra-Santana; María del Mar Romero-Alemán (Pharmaceutics)
Background/Objectives: The utility of various biocompatible biological and synthetic polymers as substrates to provide structural support, facilitate cell migration, and promote the healing of full-thickness wounds by secondary intention has been studied. This includes intelligent structures that enable the release of natural products or drugs for these and other purposes. In this study, the primary objective was to analyze and compare, from a macroscopic perspective, the individual behavior of the polymer poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), with Aloe vera (PHBV/Av) or honey (PHBV/Ho), in the healing process of a full-thickness skin wound over 40 days in a murine model, in addition to describing the microscopic ultrastructure of the nanofibers. Methods: Two experimental groups were established, PHVB/AV (n = 5) and PHVB/Ho (n = 5), along with one control group, PHBV (n = 5), all of which underwent biopsies that included the entire thickness of the skin and the panniculus carnosus of the mid-dorsal area of the mouse. Cylindrical pieces of each membrane, measuring approximately 7 × 0.2 mm, were placed in the wound bed and covered with a transparent dressing. No topical treatment was administered during the control process, nor were the implants changed during the healing period. Results: Univariate and multivariate analyses were performed. The data show that the PHBV/Ho scaffolds reduce the diameter of the wounds by 100% after 40 days (p < 0.001), compared with PHBV/Av (100%; p = 0.211) and the control group, PHBV. Conclusions: From a macroscopic perspective, the PHBV/Ho scaffold significantly accelerated wound healing when applied once to the wound bed, outperforming both the PHBV/Av composite and PHBV alone. Notably, this effect was achieved without the need for dressing changes or additional treatment during the healing period.